2018
DOI: 10.15385/jpicc.2018.8.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Historical survey of the floating mat model for the origin of Carboniferous coal beds

Abstract: For three hundred years geologists and paleobotanists have been attempting to describe the process that deposited plant material that formed Carboniferous coal beds. Autochthonous and allochthonous explanations in the early Nineteenth Century showed how scientific methodology becomes involved in coal interpretation. Autochthonous modelers used the paleobotany-strata-petrology-environment method to argue that coal is a terrestrial swamp deposit. Allochthonous modelers used the petrology-strata-paleobotany-envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Both early and later allochthonists of the French School used the "petrology-strata-paleobotany-environment" methodology to understand the origin of Carboniferous coal. The floating mat model has a robust three-hundred-year history that was summarized for the first time by Austin and Sanders (2018). About the same time as the French School of allochthonists was developing subaqueous notions for coal deposition and elaborating the drift model, another group of allochthonists already had an alternate understanding.…”
Section: Root Of Controversymentioning
confidence: 99%
See 3 more Smart Citations
“…Both early and later allochthonists of the French School used the "petrology-strata-paleobotany-environment" methodology to understand the origin of Carboniferous coal. The floating mat model has a robust three-hundred-year history that was summarized for the first time by Austin and Sanders (2018). About the same time as the French School of allochthonists was developing subaqueous notions for coal deposition and elaborating the drift model, another group of allochthonists already had an alternate understanding.…”
Section: Root Of Controversymentioning
confidence: 99%
“…Paleobotanical observations favoring the floating mat model appear in the following pages. Austin and Sanders (2018) observed that historically the drift model and the floating mat model of allochthonists used the "petrology-stratapaleobotany-environment" methodology to understand the origin of Carboniferous coal.…”
Section: Root Of Controversymentioning
confidence: 99%
See 2 more Smart Citations
“…This point of view is, however, not left unchallenged and has been hotly debated during some period of time (Gastaldo, 1999). But still in the recent past attempts have been held necessary to clarify the origin of allochthonous to parautochthonous coal deposition mainly taking a sedimentary approach Glasspool, 2003;Zengxue et al, 2006;Austin and Sanders, 2018). The current study goes technically beyond this geological approach and makes use of a further geoscientific tool, geomorphology, which is frequently sidelined in economic geology, in general.…”
Section: Introductionmentioning
confidence: 96%